An Analysis of Organizational Behavior and Teacher Performance Satisfaction in Private Madrasah Aliyah (MAS), South Tangerang City, Banten - Nuryati Djihadah; Zehan Zehan; Estiningsih Trihandayani; Ersam Mahendrawan (Hasanuddin University, 2026)
This study aims to analyze organizational behavior and its impact on teacher performance satisfaction at Private Madrasah Aliyah (MAS) in South Tangerang City. The main issue addressed in this research is the extent to which communication, leadership, organizational culture, and organizational structure contribute to the level of job satisfaction and teacher performance. The research employed a descriptive qualitative approach, with data collected through interviews, observations, questionnaires, and document analysis. The research subjects included principals, teachers, and educational staff from two private madrasahs, namely MA Jamiyyah Islamiyah and MA Al-Ikhwaniyah. The findings indicate that organizational behavior in both madrasahs falls into a good category, with a high overall average score. Effective communication, participative leadership, harmonious relationships among teachers, as well as institutional support and recognition are dominant factors that enhance teacher job satisfaction and performance. On the other hand, the balance between workload and welfare, as well as the alignment between salary and job responsibilities, still require further attention. Overall, healthy organizational behavior creates a conducive work environment, strengthens teacher motivation and loyalty, and directly contributes to improving the quality of education in the madrasah.